The Role of Villages in Implementing Quality General Elections in Indonesia (Poritibi Lama Village Study) - Syaputra, Muhammad Yusrizal Adi; Munthe, Riswan; Lubis, Anggraeini Atmei (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Village involvement in creating quality elections is the responsibility of the village government through political education of village communities. The 2020 simultaneous elections were held in 270 regions consisting of 9 provinces, 224 regencies and 37 cities throughout Indonesia. Karo Regency is one of 37 regions holding regional head elections. Karo Regency, which has 259 villages, can be seen from the general election statistical data as an area that has a very low level of community participation in elections, meaning that community involvement in exercising their political rights is not significant. The percentage of total community participation in Karo Regency has not yet reached 50 percent. This shows that the level of community participation is not yet good, because it has not been able to approach the political participation target set by the KPU of 77.5 percent. This research will examine the role of the village government in improving the quality of fair and high-quality elections, as well as examine the obstacles of the village government in implementing political education and village community participation in elections. The analytical method in this research uses empirical juridical research. Data comes from primary data. Data collection instruments are observation, documentation studies and interviews, while data analysis uses descriptive analysis. This research produces findings that the village government plays a role as a government institution that has an influence on increasing community participation through community political education, collecting community data for voter data which is submitted to the Regional General Election Commission (KPUD), conducting outreach about elections to the community, providing village security during voting. The second result shows that the village government has not implemented the function of political education for the people well. The factors that hinder the Partibilama Village Government in political education are the lack of human resources in Partibilama Village, financial factors of the village government and cultural factors of the Partibilama Community..